Current and Potential Applications of Host-Defense Peptides and Proteins in Urology. (1st March 2015) - Lo, Joey Chor Yee; Lange, Dirk
Abstract : The use of antibiotics has become increasingly disfavored as more multidrug resistant pathogens are on the rise. A promising alternative to the use of these conventional drugs includes antimicrobial peptides or host-defense peptides. These peptides typically consist of short amino acid chains with a net cationic charge and a substantial portion of hydrophobic residues. They mainly target the bacterial cell membrane but are also capable of translocating through the membrane and target intracellular components, making it difficult for bacteria to gain resistance as multiple essential cellular processes are being targeted. The use of these peptides in the field of biomedical therapies has been examined, and the different approaches to using them under various settings are constantly being discovered. In this review, we discuss the current and potential applications of these host-defense peptides in the field of urology. Besides the use of these peptides as antimicrobial agents, the value of these biological molecules has recently been expanded to their use as antitumor and anti-kidney-stone agents.